Reducing Falls in Dementia Inpatients Using Vision-Based Technology. Issue 3 (4th April 2022) - Wright, Kay; Singh, Swaran
Abstract : Objectives: Falls have a significant negative impact on the health and well-being of people with dementia and increase service costs related to staff time, paramedic visits, and accident and emergency (A&E) admissions. We examined whether a remote digital vision-based monitoring and management system had an impact on the prevention of falls. Methods: Our study was conducted within the Manor dementia inpatient wards at the Coventry and Warwickshire Partnership Trust. Data were retrieved from incident reports before and 22 months after installation of the system. We examined number of night time falls, severity of fall, number of paramedic visits and A&E admissions, and the number of enhanced observations during both time periods. Results: There was a significant 48% reduction in the number of nighttime falls ( P < 0.01), a 49% reduction in visits from paramedics ( P < 0.2), and a 68% reduction in A&E admissions ( P < 0.02). In addition, the data indicated an 82% reduction in the number of moderate severity falls and that enhanced one-to-one observation hours were reduced by 71%. Conclusions: The study demonstrated that a contact-free, remote digital vision-based monitoring and management system reduced falls, fall-related injuries, emergency services time, clinician time, and disruptive night time observations. This benefits the clinicians by allowing them to undertake other clinical duties and promotes the health and safety of patients who might normally experience injury-related stress and disruption to sleep.